A case study in the use of audio-visual media for teaching listening skills in junior high school EFL classrooms: Perceived effectiveness and challenges - Daulay, Ernita (Journal on English as a Foreign Language, 2025)
Listening skills are foundational to second and foreign language acquisition. However, traditional teaching methods often fail to address learners' challenges effectively, creating a gap in instructional approaches that support listening comprehension. This study investigated the perceived effectiveness and practical challenges of using audio-visual media to teach listening skills to junior high school students. Employing a qualitative case study design, six purposefully selected English teachers from two schools in Medan, Indonesia, participated in semi-structured interviews, providing insights into their experiences. Thematic analysis revealed that audio-visual media appear to enhance listening comprehension by integrating auditory and visual stimuli, supporting students' understanding of accents, intonations, and conversational contexts while also increasing motivation and engagement. Teachers reported that these tools make lessons more interactive and facilitate efficient material delivery. However, several challenges were identified, including technological disruptions, inadequate facilities, and variations in students' listening abilities, which hinder optimal outcomes. The findings underscore the need for improved infrastructure, targeted teacher training, and tailored instructional strategies to maximize the benefits of audio-visual tools in language education. This study highlights the potential of audio-visual media to enhance listening comprehension and engagement while emphasizing the need to address technological and instructional challenges for effective implementation.